K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NM
2 tháng 9 2021

ta có :

\(\left(25-2x\right)^3:5=2^4+3^2=16+9=25\)

hay \(\left(25-2x\right)^3=25\times5=125=5^3\Leftrightarrow25-2x=5\Leftrightarrow2x=20\)

\(\Leftrightarrow x=10\)

( 25 - 2x )3 : 5 - 24 = 32

=> ( 25 - 2x )3 : 5 - 16 = 9

=> ( 25 - 2x )3 : 5 = 25

=> ( 25 - 2x )3 = 125

=> ( 25 - 2x )3 = 53

=> 25 - 2x = 5

=> 2x = 20

=> x = 10

(25-2 x)^3:5-2^4=3^2=>(25-2x)^3:5-2^4=9=>(25-2x)^3-2^4=9×5=>(25-2x)^3-2^4=45=>(25-2x)^3=45+2^4=>(25-2x)^3=45+32=>(25-2x)^3=77=>25-2x=77^3=>25-2x=456533=>2x=25-456533=>2x=-456508=>x=-456508:2=>x=-228254
14 tháng 10 2023

a) 16 = 2⁴

42 = 2.3.7

ƯCLN(16; 42) = 2

ƯC(16; 42) = Ư(2) = {1; 2}

b) 16 = 2⁴

42 = 2.3.7

86 = 2.43

ƯCLN(16; 42; 86) = 2

ƯC(16; 42; 86) = Ư(2) = {1; 2}

c) 25 = 5²

75 = 3.5²

ƯCLN(25; 75) = 5² = 25

ƯC(25; 75) = Ư(25) = {1; 5; 25}

d) 25 = 5²

55 = 5.11

75 = 3.5²

ƯCLN(25; 55; 75) = 5

ƯC(25; 55; 75) = Ư(5) = {1; 5}

24 tháng 4 2019

a) \(2.\left(x+\frac{2}{5}\right)+1\frac{1}{4}=\frac{11}{20}\)

\(2.\left(x+\frac{2}{5}\right)+\frac{5}{4}=\frac{11}{20}\)

\(2.\left(x+\frac{2}{5}\right)=\frac{-7}{10}\)

\(x+\frac{2}{5}=\frac{-7}{20}\)

\(x=\frac{-13}{20}\)

Vậy \(x=\frac{-13}{20}\)

24 tháng 4 2019

b)\(x-1\frac{1}{8}-\frac{2}{3}x-\frac{5}{6}x=75\%\)

  \(\left(x-\frac{2}{3}x-\frac{5}{6}x\right)-\frac{9}{8}=\frac{3}{4}\)

\(\frac{-1}{2}x-\frac{9}{8}=\frac{3}{4}\)

\(\frac{-1}{2}x=\frac{15}{8}\)

\(x=\frac{-15}{4}\)

Vậy \(x=\frac{-15}{4}\)

28 tháng 9 2016

Chắc câu b sai?

 

Ta có

\(\frac{1}{2}=\frac{1\times3\times5}{2\times3\times5}=\frac{15}{30}\)

\(\frac{1}{3}=\frac{1\times2\times5}{3\times2\times5}=\frac{10}{30}\)

\(\frac{2}{5}=\frac{2\times2\times3}{5\times2\times3}=\frac{12}{30}\)

Hok tốt !!!!!!!!!!!!!!!!!!!

15 tháng 7 2019

\(\frac{x-3}{5}=\frac{x+4}{-2}\)

=> (x - 3). (-2) = 5(x + 4)

=> -2x + 6 = 5x + 20

=> -2x - 5x = 20 - 6

=> -7x = 14

=> x = 14 : (-7)

=> x = -2

15 tháng 7 2019

x-3/5=x+4/-2

=> ﴾x ‐ 3﴿. ﴾‐2﴿ = 5﴾x + 4﴿

 => ‐2x + 6 = 5x + 20 

=> ‐2x ‐ 5x = 20 ‐ 6 => ‐7x = 14 => x = 14 : ﴾‐7﴿ 

=> x = ‐2 

> =<